Studies on some rquirements for vegetative growth of two Pleurotus spp. - El-FalIal, A. A.; Nour El-Dein, M. M.; Khalil, A. E. (2003)
Effect of some physiological factors on the growth of Pleurotus columbinus and Pleurotus pulmonarius have been investigated. The tested fungi had the same optimum temperature range 25-30°C. P. columbinus was slightly more tolerant to higher temperatures than P. pulmonarius. Both fungi preferred neutral medium and widely used carbohydrates. Sucrose and galactose were the best carbon sources for P. pulmonarius and P. columbinzus, respectively. Asparagine was efficiently utilised by the two fungi. Growth response was strong at a wide range of 0.04-0.48% nitrogen in the medium which is equivalent to 32:1-2.63:1 C/N ratios
Includes references.
Summary in Arabic.
1
Keywords: Pleurotus ostreatus; Pleurotus ostreatus -- Breeding; Pleurotus ostreatus -- Physiology; Pleurotus ostreatus -- Effect of temperature on; Mushrooms -- Physiology; Mushrooms -- Nutrition